Changes in lead and chromium contents in sewage sludge evaluated using both single extractants and sequential method. Issue 1 (1st January 2020) - Jakubus, Monika
ABSTRACT: The aim of this study was to evaluate changes in lead and chromium amounts in sequentially separated fractions and available forms of four sewage sludge (SS). Lead and chromium sequential extraction in SS was performed using BCR method. Single extractants were used to assay available and bioavailable forms of metals. It was found that Pb and Cr were detected in the largest amounts in organic forms, while the lowest levels were recorded for exchangeable ones. Sewage sludges from the small installations contained significantly lower amounts of metals (both available, bioavailable and sequentially separated fractions of sewage sludge) in comparison with those originating from the large treatment installations. Generally amounts of metals detected in sewage sludge were small in the years of this study, which should be considered a positive trend. Additionally, the bioavailability index (φ) and risk assessment code (RAC) indicated no negative impact of metals contained in the analysed SS on the soil environment. GRAPHICAL ABSTRACT: uf0001